Hieracium purkynei (Asteraceae): an endemic to the Sudetes rediscovered after a century - Szeląg, Zbigniew (Phytotaxa, 2023)
Hieracium purkynei was described from specimens collected in 1884 in the Giant Mountains, Sudetes, in Czechia. Since 1914, the species was considered extinct. In 2019, two new localities of H. purkynei were found on the Polish side of the Giant Mountains. The species is illustrated with photographs of the holotype (kept at PR) and, for the first time, living plants in the field.